If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x*((6*x-9)/3)+(1/3)*x = x*((3*x-3)/4) // - x*((3*x-3)/4)
x*((6*x-9)/3)-(x*((3*x-3)/4))+(1/3)*x = 0
(x*(6*x-9))/3+(-1*x*(3*x-3))/4+x/3 = 0
(4*x*(6*x-9))/(3*4)+(-1*3*x*(3*x-3))/(3*4)+(4*x)/(3*4) = 0
4*x*(6*x-9)-1*3*x*(3*x-3)+4*x = 0
15*x^2-27*x+4*x = 0
15*x^2-23*x = 0
15*x^2-23*x = 0
x*(15*x-23) = 0
15*x-23 = 0 // + 23
15*x = 23 // : 15
x = 23/15
x*(x-23/15) = 0
(x*(x-23/15))/(3*4) = 0
(x*(x-23/15))/(3*4) = 0 // * 3*4
x*(x-23/15) = 0
( x-23/15 )
x-23/15 = 0 // + 23/15
x = 23/15
( x )
x = 0
x in { 23/15, 0 }
| 24*4= | | 3/4t+7/8t=39 | | 5-2m=3m-5 | | 4x+9y=2 | | 72/3*4-2+10=-6 | | 20b^2-245= | | 14-y=1 | | 0.20x+0.45(50)=36.5 | | h+|-8|=15 | | 2n/-5=4/6 | | 8x+7=-3+5x+19 | | 2(d+7)-(3d+5)=2d+(4d-9+3d)-(d+3) | | 1.50m+5=15.50 | | -2/3r+2r=6/5r+8/5 | | 4(3r+2)-2r=-10 | | 0.50f+5=11.50 | | -8(r+5)=-18-8r | | 3=8x+4 | | -6(2+7k)=-12+4k | | 2(n-2)=2+4n | | 4(3n-2)=64 | | -16+3y=4 | | -2=-2-3(4-2k) | | 10k+3=8k+27 | | 72=6(-2+7x) | | 55=18+0.004x | | 32=4(1-7k) | | 2a+4a-13=47 | | 4x-6=3x+1-x-7 | | -5(3x+4)=2(9-6x) | | -36=6X-12Y | | 384628x+298473=2937474 |